Corrosion Rate Estimation of Passenger Ships Ballast System Pipes - Moch Ricky Dariansyah; Mohammad Danil Arifin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Corrosion on ships is a common challenge that arises due to the exposure of various metal components to the marine environment. It is a natural electrochemical process that deteriorates the integrity and performance of the ship's structures and equipment over time. The corrosive agents in the marine environment include seawater, humidity, salt spray, chemicals, and microbiological organisms. Corrosion can affect different parts of a ship, such as the hull, ballast tanks, pipelines, propellers, rudders, and various metallic fittings. It can lead to the weakening of structural components, reduced operational efficiency, increased maintenance costs, and even safety hazards. Therefore, it is essential to determine the limitations of the lifespan and efficiency of pipes concerning the influence of corrosion. In this study, the corrosion rate of Galvanized Steel Pipe SCH 40 and Stainless Steel 304 was estimated. The corrosion rate of pipes was evaluated by variating the influence of 3% and 6% salinity and immersion time 240, 360, and 720 hours. The result shows that the corrosion rate tends to increase in higher salinity and immersion time.